Spatial and temporal variability of water productivity in the Syr Darya Basin, Central Asia - Abdullaev, Iskandar; David, S. (2004)
Application of water productivity analysis can provide clues in the search for solutions to solve water management problems of central Asia. It is in this context that this paper provides an analysis of water productivity both spatially and temporally in the cotton and rice production areas of Syr Darya Basin of central Asia. The spatial analysis includes different farm types and basin segments, and the temporal analysis includes 3 hydrological years during 1999-2001. The analysis of temporal data showed that in water-deficient years, water productivity, both in terms of supply and evapotranspiration, is higher than the same in water-abundant years. The data also show that type and size of farms have an impact on water productivity in the case of both cotton and rice. This study concludes by suggesting strategies and options for enhancing the average water productivity both in the cotton- and rice-growing areas of the Syr Darya Basin.